Thandoer Pari di KB TK Bethany School Untuk Mewujudkan Parents as A Partner - Yussanti, Dian Widi (AUDIENSI: Jurnal Pendidikan dan Perkembangan Anak, 2024)
Parents are partners with schools in educating their students, collaborating to ensure the development and success of their children's education. It is undeniable that many parents entrust their children to the school to be educated, hoping that the school can provide quality education and support their children's development. Parents are not fully aware that education is a shared responsibility between the school and parents. Thandoer Pari, 'Bethany the Doer of Parential Involvement', implemented at Bethany School's Kindergarten aims to increase parental involvement in educating their children. Thandoer Pari has been implemented since 2017 until now. This research method is a descriptive qualitative approach. Through this activity, the number of parental involvement has changed significantly. Thandoer Pari became an activity to encourage students to learn and subsequently to participate in school activities to increase. Students are happy to go to school, happy in participating in the learning and playing process, and children's growth and development can also take place optimally.